Management of Educational Facilities and Infrastructure in Improving Excellent Graduates at SMK Proklamasi Karawang - Hendra Cipto; Ardani Achmad; Endang Komara; Waska Warta (Universitas Muhammadiyah Enrekang, 2023)
Advances in knowledge and technology make schools have to adapt to changes in zama. Facilities and infrastructure are important in supporting the learning process that can create graduates from schools to become excellent graduates. Excellent graduates are expected to be in accordance with the needs of the industrial world or the needs of society in general. One of the effectiveness of learning activities in SMK is the field of facilities and infrastructure. This study aims to determine the management of educational facilities and infrastructure at SMK Proklamasi Tanjungmekar Karawang in improving superior graduates. This research uses qualitative methods with a phenomonological approach, with the research location at SMK Proklamasi Tanjungmekar Karawang. Data collection techniques are carried out through interviews, observations, and documentation studies. The data analysis technique that researchers use is data reduction, then presenting data and drawing conclusions. Based on the results of the research conducted, the management of educational facilities and infrastructure at SMK Proklamasi Tanjungmekar Karawang was obtained as follows. 1) the planning process of facilities and infrastructure implemented at SMK Proklamasi is in accordance with the established SOP, 2) the process of organizing facilities and infrastructure has been carried out in accordance with the job description well, 3) the implementation of facilities and infrastructure is running well, 4) the process of supervising facilities and infrastructure is running well